The life and lies of Paul Crouch : communist, opportunist, Cold War snitch - Taylor, Gregory S. (University Press of Florida, 2014)
Taylor traces the life of Paul Crouch (1903-1955), an infamous paid informant for the federal government during the McCarthy era. Taylor not only highlights Crouch's unusual life, but also examines the dangers of ideologues.